The Radio Counterpart to the Fast X-Ray Transient EP240414a - Joe S. Bright; Francesco Carotenuto; Rob Fender; Carmen Choza; Andrew Mummery; Peter G. Jonker; Stephen J. Smartt; David R. DeBoer; Wael Farah; James Matthews; Alexander W. Pollak; Lauren Rhodes; et al. (The Astrophysical Journal)
Despite being operational for only a short time, the Einstein Probe mission, with its large field of view and rapid localization capabilities, has already significantly advanced the study of rapid variability in the soft X-ray sky. We report the discovery of luminous and variable radio emission from the Einstein Probe fast X-ray transient EP240414a, the second such source with a radio counterpart. The radio emission at 3 GHz peaks at ∼30 days postexplosion and with a spectral luminosity ∼2 × 10 ^30 erg s ^−1 Hz ^−1 , similar to what is seen from long gamma-ray bursts, and distinct from other extragalactic transients including supernovae and tidal disruption events, although we cannot completely rule out emission from engine driven stellar explosions, e.g., the fast blue optical transients. An equipartition analysis of our radio data reveals that an outflow with at least a moderate bulk Lorentz factor (Γ ≳ 1.6) with a minimum energy of ∼10 ^48 erg is required to explain our observations. The apparent lack of a reported gamma-ray counterpart to EP240414a could suggest that an off-axis or choked jet could be responsible for the radio emission, although a low-luminosity gamma-ray burst may have gone undetected. Our observations are consistent with the hypothesis that a significant fraction of extragalactic fast X-ray transients are associated with the deaths of massive stars.